TRANSPLANTATION OF CRYOPRESERVED FETAL LIVER CELLS SEEDED INTO MACROPOROUS ALGINATE-GELATIN SCAFFOLDS IN RATS WITH LIVER FAILURE - D. V. Grizay; A. S. Lebedinsky; O. V. Ochenashko; O. Yu. Rogulska; Yu. A. Petrenko; V. I. Lozinsky; R. V. Ivanov; A. Yu. Petrenko (Вестник трансплантологии и искусственных органов, 2015)
Aim. To study the therapeutic potential of cryopreserved fetal liver cells seeded into macroporous alginategelatin scaffolds after implantation to omentum of rats with hepatic failure.Materials and methods.Hepatic failure was simulated by administration of 2-acetyl aminofl uorene followed partial hepatectomy. Macroporous alginate-gelatin scaffolds, seeded with allogenic cryopreserved fetal liver cells (FLCs) were implanted into rat omentum. To prevent from colonization of host cells scaffolds were coated with alginate gel shell. Serum transaminase activity, levels of albumin and bilirubin as markers of hepatic function were determined during 4 weeks after failure model formation and scaffold implantation. Morphology of liver and scaffolds after implantation were examined histologically. Results. Macroporous alginate-gelatin scaffolds after implantation to healthy rats were colonized by host cells. Additional formation of alginate gel shell around scaffolds prevented the colonization. Implantation of macroporous scaffolds seeded with cryopreserved rat FLCs and additionally coated with alginate gel shell into omentum of rats with hepatic failure resulted in signifi cant improvement of hepatospecifi c parameters of the blood serum and positive changes of liver morphology. The presence of cells with their extracellular matrix within the scaffolds was confi rmed after 4 weeks post implantation.Conclusion. The data above indicate that macroporous alginate-gelatin scaffolds coated with alginate gel shell are promising cell carriers for the development of bioengineered liver equivalents.